WORKSHOP PEMBUATAN KONTEN DIGITAL UNTUK PUBLIKASI POTENSI NAGARI SARIAK LAWEH KABUPATEN LIMA PULUH KOTA - Ulfia Rahmi; Rery Novio; Azrul Azrul (Jurnal Terapan Abdimas, 2025)
Abstract. Digital content is not only a means of information but also builds a positive image of the village. Through the presentation of interesting and informative content, the village can attract the attention of tourists, investors, and other parties who have the potential to support village development. Sariak Laweh Village/Nagari has the potential for digital-based services including information centers, social media since, and integrated electronic signature correspondence services from BSRE. Sariak Laweh Village needs strengthening in the development of digital content and information, so that the exposure of the village's potential can also be done by the community through existing websites or social media. For this reason, a Digital Content Creation Workshop was held, a digital content training aimed at ensuring that village officials know how to identify the village's potential and can publish this potential through digital content on the official website and social media. The activity consists of three steps, namely training, guided production, and publication on the website and social media. The results show that most of the devices understand how to identify the village's potential, and all village devices can produce digital content but need to improve the quality of the display to be worthy of publication. Based on these results, it can be concluded that the objectives of the workshop were achieved with the recommendation that the village devices need to improve their content both in quantity and quality.   Abstrak. Konten digital tidak hanya menjadi sarana informasi, tetapi juga membangun citra positif nagari/desa. Melalui penyajian konten yang menarik dan informatif, desa dapat menarik perhatian wisatawan, investor, dan pihak lain yang berpotensi mendukung pengembangan desa. Desa/Nagari Sariak Laweh memiliki potensi layanan berbasis digital meliputi pusat informasi, media sosial sejak, dan layanan persuratan terintegrasi Tanda Tangan Elektronik dari BSRE. Nagari Sariak Laweh membutuhkan penguatan dalam pengembangan konten dan informasi digital, agar ekspos potensi nagari juga bisa dilakukan oleh masyarakat melalui media website ataupun media sosial yang ada. Untuk itu dilaksanakan Workshop Pembuatan Konten Digital Pelatihan konten digital yang bertujuan agar perangkat desa mengetahui bagaimana cara mengidentifikasi potensi nagari dan mempu mempublikasikan potensi tersebut melalui konten digital di website resmi dan media sosial. Kegiatan terdiri dari tiga langkah yaitu pelatihan, produksi terbimbing, dan publikasi di website serta media sosial. Hasilnya menunjukkan bahwa Sebagian besar perangkat memahami bagaimana mengidentifikasi potensi nagari dan semua perangkat desa mampu memproduksi konten digital namun perlu peningkatan kualitas tampilan untuk layak dipublikasikan. Berdasarkan hasil tersebut dapat disimpulkan tujuan workshop tercapai dengan rekomendasi bahwa perangkat nagari perlu meningkatkan kontennya baik secara kuantitas maupun kualitas.